Higher Triglyceride–Glucose Index Is Associated With Increased Likelihood of Kidney Stones - Qin, Zheng; Zhao, Junjie; Geng, Jiwen; Chang, Kaixi; Liao, Ruoxi; Su, Baihai (Frontiers in Endocrinology, 2021)
Aims We aimed to assess the association between triglyceride–glucose (TyG) index and kidney stones in US adults. Methods Data were obtained from the 2007–2014 National Health and Nutrition Examination Survey (NHANES). Participants aged ≥18 years who were not pregnant and provided complete data about TyG index and kidney stones were included in the analysis. Weighted multivariable regression analysis and subgroup analysis were preformed to estimate the independent relationship between TyG index and nephrolithiasis and recurrence. Results A total of 20,972 participants were included with the mean TyG index of 8.71 ± 0.72. The prevalence rates of nephrolithiasis and recurrence were 9.30% and 3.17% overall and increased with the higher TyG index tertiles (Nephrolithiasis: Tertile 1, 6.98%; Tertile 2, 9.15%; Tertile 3, 11.98%, p < 0.01; Recurrence: Tertile 1, 1.84%; Tertile 2, 3.27%; Tertile 3, 4.50%, p < 0.01). Each unit increase in TyG index was associated with 12% and 26% higher odds of nephrolithiasis [odds ratio (OR) = 1.12; 95% CI: 1.02–1.22; p = 0.02] and recurrence (OR = 1.26; 95% CI: 1.08–1.46; p < 0.01). Interaction tests indicated no significant effect of gender, age, body mass index, hypertension, and diabetes on this association between TyG index and kidney stones. Conclusions Higher TyG index was associated with an increased likelihood of nephrolithiasis and recurrence. Considering TyG index is a reliable indicator of insulin resistance (IR). Treatment and management of IR at a younger age may improve or alleviate the occurrence and recurrence of kidney stones.